Multimodal single-cell profiling reveals neuronal vulnerability and pathological cell states in focal cortical dysplasia - Isabella C. Galvão; Manuela Lemoine; Lauana A. Messias; Patrícia A.O.R.A. Araújo; Jaqueline C. Geraldis; Clarissa L. Yasuda; Marina K.M. Alvim; Enrico Ghizoni; Helder Tedeschi; Fernando Cendes; Fabio Rogerio; Iscia Lopes-Cendes; et al. (iScience)
Summary: Focal cortical dysplasia (FCD) is a neurodevelopmental condition characterized by malformations of the cerebral cortex that often cause drug-resistant epilepsy. In this study, we performed multi-omics single-nuclei profiling to map the chromatin accessibility and transcriptome landscapes of FCD type II, generating a comprehensive multimodal single-nuclei dataset comprising 61,525 cells from 11 clinical samples of lesions and controls. Our findings revealed profound chromatin, transcriptomic, and cellular alterations affecting neuronal and glial cells in FCD lesions, including the selective loss of upper-layer excitatory neurons, significant expansion of oligodendrocytes and immature astrocytic populations, and a distinct neuronal subpopulation harboring dysmorphic neurons. Furthermore, we uncovered activated microglia subsets, particularly in FCD IIb cases. This comprehensive study unveils neuronal and glial cell states driving FCD development and epileptogenicity, enhancing our understanding of FCD and offering directions for targeted therapy development.